Melampaui Cerita-Cerita Kematian di Kalangan Abangan: Agama dan Mitos - Larasati, Yuniar Galuh; Fernando, Henky; Morin, Leanne (Reformed Center for Religion and Society, 2025)
This study examines the construction of death myths through eschatological concepts within the religious beliefs of the Abangan Javanese community, a subcultural group with a syncretic religious orientation rooted in Kejawen traditions. The primary issue addressed is the scarcity of scholarly attention to how localized eschatological narratives shape alternative interpretations of death, which are often overlooked by dominant religious paradigms. Employing a qualitative descriptive method with a case study approach, this research is grounded in theoretical frameworks of eschatology and religiosity to analyze how the abangan community constructs meaning around death. The findings reveal that death is not solely understood as a personal or moral endpoint but is perceived as the result of broader socio-religious dynamics, environmental conditions, and interactions with unseen entities. These interpretations reflect a unique epistemology that challenges normative theological discourses and affirms the validity of local spiritual worldviews. This study contributes to eschatological scholarship by highlighting the interpretive richness of indigenous belief systems and addressing the ongoing marginalization of religious knowledge within broader academic and theological discussions.